On Improving Urban Environment Representations - Pueyo, Xavier; Bosch, Carles; Patow, Gustavo A. (Frontiers in Robotics and AI, 2014)
Computer Graphics has evolved into a mature and powerful field that offers many opportunities to enhance different disciplines, adapting to the specific needs of each. One of these important fields is the design and analysis of Urban Environments. In this article we try to offer a perspective of one of the sectors identified in Urban Environment studies: Urbanization. More precisely we focus on geometric and appearance modeling, rendering and simulation tools to help stakeholders in key decision stages of the process.